2022
DOI: 10.1186/s13034-022-00445-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of a transdiagnostic universal prevention program for both internalizing and externalizing problems in children: two feasibility studies

Abstract: Background The present study examined the effectiveness of the Universal Unified Prevention Program for Diverse Disorders (Up2-D2) for internalizing and externalizing problems for children aged 9–11 years. Methods We used two feasibility studies. The Up2-D2 entailed 12 sessions delivered by teachers; each session was developed based on cognitive-behavioral and positive psychological interventions. In Studies 1 and 2, 58 elementary school children a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Therefore, students came back to school after school closure might have more anxiety at the moment and it might be associated with the outcome of this study. Besides, Kishida et al’s ( 2022 ) analysis of feasibility studies using the Up2-D2 for whole students in elementary schools indicated significant improvements for general difficulties which include both internalizing and externalizing problems, but no significant improvements in anxiety, depression, and anger. Although this program was developed to aim preventive effects for anxiety, depression, and anger as a transdiagnostic intervention, pragmatic trials in schools supported that anxiety or general difficulties might be highly likely to be improved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, students came back to school after school closure might have more anxiety at the moment and it might be associated with the outcome of this study. Besides, Kishida et al’s ( 2022 ) analysis of feasibility studies using the Up2-D2 for whole students in elementary schools indicated significant improvements for general difficulties which include both internalizing and externalizing problems, but no significant improvements in anxiety, depression, and anger. Although this program was developed to aim preventive effects for anxiety, depression, and anger as a transdiagnostic intervention, pragmatic trials in schools supported that anxiety or general difficulties might be highly likely to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a teacher manual (teaching plan) was created and distributed so that teachers could implement the program without intensive training and supervision by mental health experts. Kishida et al, ( 2022 ) confirmed that the program could be feasible when implemented without on-site training and ongoing supervision by mental health experts. However, the program has been shown to be more effective when training and supervision was provided by experts rather than schoolteachers who have not been trained (Kishida et al, 2022 ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…WEMWBS Baseline, post-intervention, 3-months follow-up, 9-months follow-up Teacher Mindfuleness Significant effect on Decentering and Nonreactivity (d = − 0.20) among the general sample in 3 month follow-up. Year 8 at 3 month follow-up: Awareness of External Experiences (d = − 0.30), Decentering and Nonreactivity (d = − 0.39), wellbeing (d = − 0.25) Promotion Secondary Kishida et al [ 77 ] (81.3%) No randomization was conducted JSDQ GSESC_x005f-R Short CAS. DSRS-C ASCA Baseline, post-intervention Teacher CBT Study 1: Significant time effects for general difficulties [F (1, 52.78) = 4.88, p < 0.05], general difficulties (SDQ) decreased with small effect sizes (g = − 0.20).…”
Section: Methodsmentioning
confidence: 99%